2022
DOI: 10.3390/fire5060211
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Fire Severity and Post-Fire Vegetation Recovery in the Temperate Andes Using Earth Observation Data

Abstract: In wildfire areas, earth observation data is used for the development of fire-severity maps or vegetation recovery to select post-fire measures for erosion control and revegetation. Appropriate vegetation indices for post-fire monitoring vary with vegetation type and climate zone. This study aimed to select the best vegetation indices for post-fire vegetation monitoring using remote sensing and classification methods for the temperate zone in southern Ecuador, as well as to analyze the vegetation’s development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The authors concluded that the most reliable vegetation indices for monitoring post-fire vegetation recovery were the Leaf Chlorophyll Content Index (LCCI) and Normalized Difference Red-Edge and SWIR2 (NDRESWIR). They also observed that vegetation recovered to a great extent within the In a similar study also conducted in southern Ecuador, Maxwald et al [9] identified the most reliable vegetation indices for post-fire vegetation monitoring, and analyzed vegetation recovery across different classes of fire severity. The authors concluded that the most reliable vegetation indices for monitoring post-fire vegetation recovery were the Leaf Chlorophyll Content Index (LCCI) and Normalized Difference Red-Edge and SWIR2 (NDRESWIR).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The authors concluded that the most reliable vegetation indices for monitoring post-fire vegetation recovery were the Leaf Chlorophyll Content Index (LCCI) and Normalized Difference Red-Edge and SWIR2 (NDRESWIR). They also observed that vegetation recovered to a great extent within the In a similar study also conducted in southern Ecuador, Maxwald et al [9] identified the most reliable vegetation indices for post-fire vegetation monitoring, and analyzed vegetation recovery across different classes of fire severity. The authors concluded that the most reliable vegetation indices for monitoring post-fire vegetation recovery were the Leaf Chlorophyll Content Index (LCCI) and Normalized Difference Red-Edge and SWIR2 (NDRESWIR).…”
mentioning
confidence: 94%
“…In a similar study also conducted in southern Ecuador, Maxwald et al [9] identified the most reliable vegetation indices for post-fire vegetation monitoring, and analyzed vegetation recovery across different classes of fire severity. The authors concluded that the most reliable vegetation indices for monitoring post-fire vegetation recovery were the Leaf Chlorophyll Content Index (LCCI) and Normalized Difference Red-Edge and SWIR2 (NDRESWIR).…”
mentioning
confidence: 99%
“…This study of post-fire recovery concepts is very important to understand this phenomenon. There are some different approaches to define recovery processes, including utilizing the strong performance and suitability of the post-fire stability index [20]; random forest classification models that use the fire severity classes (from the Relativized Burn Ratio (RBR)) as a dependent variable and 23 multitemporal vegetation indices [21]; post-fire stream water responses observed in watersheds [22]; multiple factors of a forest's recovery rate post-wildfire such as fire severity, tree species characteristics, topography, hydrology, soil properties, and climate [23]; and a composing study based on a Tasseled Cap linear regression trend in a post-wildfire study site [24].…”
Section: Introductionmentioning
confidence: 99%